Non-fragile mixed H-infinity and passivity control for neural networks with successive time-varying delay components - Rajavel, Sathasivam; Samidurai, Rajendran; Kilbert, Sebastiyan Anthuvan Jerome Anthuvan Jerome; Cao, Jinde; Alsaedi, Ahmed (Nonlinear Analysis: Modelling and Control, 2018)
This paper is concerned with the problem of nonfragile mixed H∞ and passivity control for neural networks with successive time-varying delay components. We construct a suitable Lyapunov–Krasovskii function with triple and quadruple integral terms then utilizing Jensen’s lemma and Wirtinger-type inequality technique. Some sufficient conditions are presented for the existence of nonfragile mixed H∞ and passivity performance criterions. The expressions for the nonfragile controller can be obtained by solving a set of linear matrix inequality. Finally, two numerical examples are presented to demonstrate the effectiveness of our proposed method.